Before and after therapeutic abortion - Mackenzie, Paul (1974)
Surveys conducted after therapeutic abortion were used to evaluate contraceptive use, to assess early physical and emotional effects and to provide feedback to the hospital nurses on their counselling role. The follow-up rate was only 53%. Of those who cooperated 82.9% were using effective contraception three months after abortion. Subjective morbidity was greater than anticipated. The main emotional response was relief coupled with some guilt and depression in a significant minority. The occurrence and significance of the after effects of abortion should be explained in advance. Training workshops for abortion counsellors would be useful. The surgical termination of pregnancy is only a small part of a comprehensive abortion service.